2007
DOI: 10.1088/1748-6041/2/1/s02
|View full text |Cite
|
Sign up to set email alerts
|

Electrode–tissues interface: modeling and experimental validation

Abstract: The electrode-tissues interface (ETI) is one of the key issues in implantable devices such as stimulators and sensors. Once the stimulator is implanted, safety and reliability become more and more critical. In this case, modeling and monitoring of the ETI are required. We propose an empirical model for the ETI and a dedicated integrated circuit to measure its corresponding complex impedance. These measurements in the frequency range of 1 Hz to 100 kHz were achieved in acute dog experiments. The model demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…The onset of non-linearity may therefore be gradual, and start very early at very limited areas on the electrode surface (e.g., it has been shown that very weak non-linearity is measurable at voltages than 100 mV). Hence, it may be difficult to differentiate between the non-linearity of the electrode processes and the tissue processes [61].…”
Section: Discussionmentioning
confidence: 99%
“…The onset of non-linearity may therefore be gradual, and start very early at very limited areas on the electrode surface (e.g., it has been shown that very weak non-linearity is measurable at voltages than 100 mV). Hence, it may be difficult to differentiate between the non-linearity of the electrode processes and the tissue processes [61].…”
Section: Discussionmentioning
confidence: 99%
“…Cs is all the shunt capacitance to the ground comprises the capacitance from the metal of the electrode to the solution through the insulation (Figure 3.17) [31,160].…”
Section: Equivalent Circuit Modelmentioning
confidence: 99%
“…Changes also depend on different parameters such as the electrode material and surface, and the amount of charge injection, as well as the physiological conditions of tissues. The ETI variations were the subject of several characterisation studies [2] which are usually based on different equivalent circuit models that describe its electrical behaviour [3]. However, measurement of these parameters requires bulky instrumentations, computers, scopes, etc [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary then to monitor its long term evolution in order to adjust the stimulation parameters to increase safety and efficiency during chronic experiments. Recently, implantable measurement devices have been developed to monitor AC and DC impedances and stimulation thresholds, [1,3,5]. However, restrictions of power and space on implants make the ETI monitoring difficult and insufficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation